Effective techniques to improve students' writing proficiency in the field of nautical science (International Journal of Food and Nutritional Sciences, 2022)
This article focused on research-based strategies for enhancing the writing skills of students studying for a B.Sc. in Nautical Science as a Degree course. Many students in the course of nautical science are proficient in speaking English but fail to write meaningful sentences. For these students, writing is quite challenging. Writing is one of the most essential skills to acquire if you want to succeed in a text-based society. Because of this change, both mainstream and ESL teachers are searching for methods to assist their students in improving their writing skills. The results of this study helped students improve their writing skills by showing them how to do it well.